Adipokines in young survivors of childhood acute lymphocytic leukemia revisited: beyond fat mass - Adriana Aparecida Siviero-Miachon; Angela Maria Spinola-Castro; Solange Andreoni; Maria Lucia de Martino Lee; Antonio Ramos Calixto; Bruno Geloneze; Gil Guerra-Junior (Korean Society of Pediatric Endocrinology, 2020)
Purpose This cross-sectional study evaluated the relationship between adipokines (leptin, adiponectin, visfatin, and resistin) and adiposity indexes regarding sex and cranial radiotherapy exposure among young acute lymphocytic leukemia survivors. Methods A multivariate analysis of covariance (MANCOVA) was used to evaluate the joint effect of sex, cranial radiotherapy, and body mass index (BMI) z-score (model 1) or fat mass index (FMI) (model 2) on adipokines. Results This study included 55 survivors of childhood acute lymphocytic leukemia between 15 and 23 years of age from both sexes (56.4% female); 43.6% of the sample had undergone cranial radiotherapy (18-24 Gy). The BMI z-score, the FMI, and sex (P<0.050 for all) influenced at least one adipokine, while cranial radiotherapy exposure was marginal in model 2. Parameter estimates from the MANCOVA's final model showed that the BMI z-score (β=-0.437, P=0.010) and the FMI (β=-0.209, P=0.004) negatively influenced adiponectin, while the FMI positively affected resistin (β=0.142, P=0.020). The relationship between leptin, visfatin, and the adiposity ndexes could not be established. In model 1, females presented with increased adiponectin (β=-1.014, P=0.011) and resistin (β=-1.067, P=0.002) levels; in model 2, female sex positively affected adiponectin (β=-1.515, P=0.001) and marginally influenced resistin (β=-0.707, P=0.054) levels. Cranial radiotherapy negatively determined visfatin levels in both final models (P<0.050). Conclusions Changes in body fat may be associated with adipose tissue dysfunction and should be carefully evaluated in survivors of acute lymphocytic leukemia, considering both sex and cranial radiotherapy exposure, to treat disorders that may possibly aggravate their risk for early cardiovascular disease.